Effects of Different Combinations of Sugar and Starch Concentrations on Ruminal Fermentation and Bacterial-Community Composition in vitro - Dong, Jia-nan; Li, Song-ze; Chen, Xue; Qin, Gui-xin; Wang, Tao; Sun, Zhe; Wu, Di; Zhao, Wei; Demelash, Natnael; Zhang, Xue-feng; Zhen, Yu-guo (Frontiers in Nutrition, 2021)
High levels of starch is known to have positive effects on both energy supply and milk yield but increases the risk of rumen acidosis. The use of sugar as a non-structural carbohydrate could circumvent this risk while maintaining the benefits, but its effects and that of the simultaneous use of both sugar and starch are not as well understood. This study aimed to evaluate the effects of different combinations of sugar and starch concentrations on ruminal fermentation and bacterial community composition in vitro in a 4×4 factorial experiment. Sixteen dietary treatments were formulated with 4 levels of sugar (6, 8, 10, and 12 % of dietary dry matter), and 4 levels of starch (21, 23, 25, and 27 % of dietary dry matter). Samples were taken at 0.5, 1, 3, 6, 12, and 24 h after cultivation to determine the disappearance rate of dry matter, rumen fermentation parameters and bacterial community composition. Butyric acid, gas production, and Treponema abundance were significantly influenced by the sugar level. The pH, acetic acid and propionic acid levels were significantly influenced by starch levels. However, the interactive effect of sugar and starch was only observed on the rate of dry matter disappearance. Furthermore, different combinations of starch and sugar had different effects on volatile fatty acid production rate, gas production rate, and dry matter disappearance rate. The production rate of rumen fermentation parameters in the high sugar group was higher. Additionally, increasing the sugar content in the diet did not change the main phylum composition in the rumen, but significantly increased the relative abundance of Bacteroidetes and Firmicutes phyla, while the relative abundance of Proteobacteria was reduced. At the genus level, the high glucose group showed significantly higher relative abundance of Treponema (P<0.05) and significantly lower relative abundance of Ruminobacter, Ruminococcus, and Streptococcus (P<0.05). In conclusion, different combinations of sugar and starch concentrations have inconsistent effects on rumen fermentation characteristics, suggesting that the starch in diets cannot be simply replaced with sugar; the combined effects of sugar and starch should be considered to improve the feed utilization rate.